Anaesthesia Management of Caesarean Section in Two Patients with Eisenmenger's Syndrome. (26th September 2011) - Fang, G.; Tian, Y. K.; Mei, W.
Abstract : Recently two parturients with Eisenmenger's syndrome underwent caesarean section at our hospital. They were managed by a multidisciplinary team during their perioperative period. The caesarean sections were uneventfully performed, one under general anaesthesia and one with epidural anaesthesia, with delivery of two newborns with satisfactory Apgar scores. One patient died in the post-partum period, and the other did well. We discuss the anaesthetic considerations in managing these high-risk patients.